(untitled) (Salud, Arte y Cuidado, 2019)
Objective: To demonstrate the relationship between glycemic control and cardiovascular autonomic neuropathy in diabetic patients who attended the diabetes office of the "Dr. Adolfo Pons" hospital. Material and method: A prospective, descriptive, correlational and transversal research was carried out, with a non experimental design; whos esample consisted of diabetics of both genders between 18 and 75 years old. Patients were assigned to two study groups with poor glycemic control (HbA1c ≥7%) or well controlled (HbA1c ˂7%) and were evaluated for CAN using three different diagnostic tests: measurement of heart rate (HR) at rest, the detection of orthostatic hypotension and the measurement of the corrected QT interval; then the variables were correlated using the Pearson correlation analysis. Results: The average age was 43.25 ± 14.71 years, predominantly of female gender in both study groups. The CAN hadan incidence of 43%, evidenced in 6 controlled patients and 20 un controlled patients (P = 0.00), the HR at rest was abnormal in 10 controlled patients and 18 uncontrolled (P = 0.03), orthostatic hypotension was detected in 6 controlled patients and 15 uncontrolled patients (P = 0.01); and QTc was prolonged in 6 controlled patients and 18 uncontrolled (P = 0.00). When correlating the variables there was a highly ignificant association (P = 0.00). Conclusion: Poor glycemic control is associated with a higher incidence of cardiovascular autonomic neuropathy. Likewise, there is a positive relations between HbA1c and the parameters of CAN assessment in diabetic patients